2019
DOI: 10.1111/ens.12346
|View full text |Cite
|
Sign up to set email alerts
|

Insect assemblages attacking seeds and fruits in a rainforest in Thailand

Abstract: Insect seed predators are important agents of mortality for tropical trees, but little is known about the impact of these herbivores in rainforests. During 3 years at Khao Chong (KHC) in southern Thailand we reared 17,555 insects from 343.2 kg or 39,252 seeds/fruits representing 357 liana and tree species. A commented list of the 243 insect species identified is provided, with details about their host plants. We observed the following. (i) Approximately 43% of identified species can be considered pests. Most w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…Bugs (Lygaeidae) feed on seeds of figs (Moraceae) (Slater 1972). Much remains to be learned about tropical seed herbivores (Basset et al 2019).…”
Section: Tropical Ecosystem Herbivores Of Reproductive Structuresmentioning
confidence: 99%
“…Bugs (Lygaeidae) feed on seeds of figs (Moraceae) (Slater 1972). Much remains to be learned about tropical seed herbivores (Basset et al 2019).…”
Section: Tropical Ecosystem Herbivores Of Reproductive Structuresmentioning
confidence: 99%
“…We have not found any other report of P. sackenii in other Lauraceae species. However, Basset et al (2019) found several individuals of 4 undetermined species of Ptecticus in fruits of a Lauraceae species in a tropical rainforest in Thailand.…”
Section: Ptecticus Sackenii Williston 1885mentioning
confidence: 99%